2022
DOI: 10.1166/jbn.2022.3472
|View full text |Cite
|
Sign up to set email alerts
|

Icariin-Mediated miR-875-5p Inhibits Autophagy and Epithelial-Mesenchymal Transition by Regulation of MDM4 in Cervical Cancer

Abstract: MicroRNAs, one type of non-coding RNA, and Icariin have attracted tremendous attention concerning various diseases, especially cancers. Also, the function of Icariin on malignant behaviors by targeting miR-875-5p/MDM4 axis in cervical cancer remains unknown. MiR-875-5p analogs combined with MDM4 or Icariin were used to explore autophagy and epithelial-mesenchymal transition in cancer cells. Xenograft mice were highlighted to elucidate the influences of Icariin and miR-875-5p in vivo. As a result, miR-875-5p w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The study further revealed that icariin exerted its effects through the impairment of the TLR4/MyD88/NF-κB and Wnt/β-catenin pathways [147]. In another study, the role of icariin in modulating malignant behaviors by targeting the miR-875-5p/MDM4 axis in cervical cancer was investigated [148]. The study revealed downregulation of miR-875-5p in cervical cancer cells, promoting malignant phenotypes and autophagy and inhibiting apoptosis [148].…”
Section: Structural Similarity Search Of the Potential Candidatesmentioning
confidence: 98%
See 2 more Smart Citations
“…The study further revealed that icariin exerted its effects through the impairment of the TLR4/MyD88/NF-κB and Wnt/β-catenin pathways [147]. In another study, the role of icariin in modulating malignant behaviors by targeting the miR-875-5p/MDM4 axis in cervical cancer was investigated [148]. The study revealed downregulation of miR-875-5p in cervical cancer cells, promoting malignant phenotypes and autophagy and inhibiting apoptosis [148].…”
Section: Structural Similarity Search Of the Potential Candidatesmentioning
confidence: 98%
“…MiR-875-5p was identified as a sponge for MDM4, and elevated MDM4 expression attenuated the impact of miR-875-5p mimic on autophagy and epithelial-mesenchymal transition. However, icariin was found to counteract the inhibitory effects of miR-875-5p inhibitor on autophagy and xenograft tumor growth [148]. These suggest that ZINC000013380012 may serve as a promising lead molecule for the development of cervical cancer therapy, offering a potential alternative to current treatment modalities.…”
Section: Structural Similarity Search Of the Potential Candidatesmentioning
confidence: 99%
See 1 more Smart Citation